2013
DOI: 10.1016/j.meddos.2013.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Multifield optimization intensity-modulated proton therapy (MFO-IMPT) for prostate cancer: Robustness analysis through simulation of rotational and translational alignment errors

Abstract: Purpose To evaluate the dosimetric consequences of rotational and translational alignment errors in patients receiving intensity-modulated proton therapy with multi-field optimization (MFO-IMPT) for prostate cancer. Materials and Methods Ten control patients with localized prostate cancer underwent treatment planning for MFO-IMPT. Rotational and translation errors were simulated along each of three axes: anterior–posterior (A-P), superior–inferior (S-I), and left–right. Results Clinical target volume (CTV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…2010, Pugh et al , 2013; Liu et al , 2014; Li et al , 2014; Lomax et al , 2004; Stuschke et al , 2012). The demand for IMPT is rapidly increasing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2010, Pugh et al , 2013; Liu et al , 2014; Li et al , 2014; Lomax et al , 2004; Stuschke et al , 2012). The demand for IMPT is rapidly increasing.…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out by many other researchers (Albertini et al , 2007; Albertini et al , 2010; Oelfke and Bortfeld, 2000; Lomax, 1999), IMPT plans may be even more degenerate than intensity-modulated radiation therapy plan (Alber et al , 2002; Jorge et al , 2004; Webb, 2003), because IMPT has one more degree of freedom, i.e., the range of protons, than intensity-modulated radiation therapy. For IMPT plans with multi-field optimization (Pugh et al , 2013), intensities of scanning spots at different two-dimensional positions in different energy layers from different treatment beam angles are independently modulated and optimized. It is likely to find certain treatment plans to achieve desired dose distributions by specifically devising optimization models such as the energy-constrained model we implemented in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For IMPT, a scanning target volume margin was applied as follows: 12 mm laterally and 6 mm in all other dimensions, except 4 to 5 mm posteriorly to the CTV. The IMPT treatment-planning technique and robustness have been described previously [16][17][18][19][20]. The total prescribed dose was 75.6 to 78 Gy (RBE), delivered in equivalent 1.8 to 2 Gy (RBE) fractions.…”
Section: Treatment Planning Techniquementioning
confidence: 99%
“…Several prior studies have examined the robustness of proton therapy plans for patients receiving radiotherapy to the prostate, seminal vesicles, and/or the pelvic lymph nodes [16][17][18][19][20]. The results of these studies have identified strategies to optimize proton therapy delivery through selection of beam angles less sensitive to patient setup error, modification of planning optimization techniques, or patient alignment strategies that minimize displacement of internal pelvic anatomy (e.g.…”
Section: Discussionmentioning
confidence: 99%